2019
DOI: 10.1007/s42452-019-0347-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling runoff and sediment yield of Kesem dam watershed, Awash basin, Ethiopia

Abstract: Runoff and sediment yield modeling is important in the watershed to alleviate soil erosion and reservoir sedimentation. This paper presents runoff and sediment yield modeling of Kesem dam watershed, which has a drainage area of 2660 km 2. Soil and Water Assessment Tool (SWAT, version 2009) integrated with ArcGIS software (version 9.3) was used to simulate the stream flow and sediment concentration of Kesem dam watershed situated in Awash River basin for the period from 1994 to 2010. The model was calibrated ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…In this study, the main reasons for choosing the SWAT model are (1) The spatial and non-spatial data required by the model are available at the desired resolution (2) The model and its manual are non-commercial. (3) The performance of the model for surface runoff simulation in different watersheds of Ethiopia is appreciated and recommended [ 5 , 19 , [42] , [43] , [44] ]. (4) The continuous time-based properties of the SWAT model can allow runoff prediction at user defined temporal resolution.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the main reasons for choosing the SWAT model are (1) The spatial and non-spatial data required by the model are available at the desired resolution (2) The model and its manual are non-commercial. (3) The performance of the model for surface runoff simulation in different watersheds of Ethiopia is appreciated and recommended [ 5 , 19 , [42] , [43] , [44] ]. (4) The continuous time-based properties of the SWAT model can allow runoff prediction at user defined temporal resolution.…”
Section: Methodsmentioning
confidence: 99%
“…Awash Basin Authority 2017 reports and strategic plan and five articles (Abebe & Gebremariam, 2019;Jilo et al, 2019;Naqvi et al, 2019;Tibebe & Bewket, 2011;Zeberie, 2020) were chosen to assess land cover impacts on sediment loss. The literature employed various techniques to detect land cover and its relation with hydrological regimes (Fig.…”
Section: Methods and Data Analysesmentioning
confidence: 99%
“…The higher agriculture expansion attributed to the change in hydrological flow variables such as increased maximum flow, wet season flow, and the minimum and the dry seasonal flow decreased over the study period. In Kessem Dam watershed, variable sediment yield and runoff across the subbasins were observed to the weight of LC in the subbasin and other initiatives factors; however, the higher sediment yield in rangebrush and agricultural land (Abebe & Gebremariam, 2019). Another study by Tadese et al (2020a) identified land cover change and future climate variation in the whole basin; furthermore, Middle and Lower basins decrease water availability and increase potential evapotranspiration.…”
Section: Middle Basinmentioning
confidence: 97%
“…With this respect, the hydrological model which is soil water assessment tool (SWAT) and geographic information system (GIS) facilities were extensively used. The model was used in Ethiopia in the watershed or sub-watershed level (Welde and Gebremariam, 2017;Abebe and Gebremariam, 2019;Setegn et al, 2009;Mengistu and Sorteberg, 2012). The SWAT is a distributed parameter model designed to simulate water, sediment in watersheds and large river basins with varying climatic conditions, soil properties, stream channel characteristics, land use and agricultural management practices 1998).…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%